Deep Learning Approach Towards T-Rex Game - Shaikh, Abujar; Sampath, AK; Choudhary, Anupam (International Journal of Computer Sciences and Engineering, 2020)
In this project, we enforce both feature-extraction based totally algorithms and an end-to-cease deep reinforcement mastering technique to discover ways to control Chrome offline dinosaur recreation directly from high- dimensional sport display input. Results display that as compared with the pixel function based totally algorithms, deep reinforcement learning is more effective and effective. It leverages the high-dimensional sensory input immediately and avoids capability errors in characteristic extraction. Finally, we recommend special schooling strategies to address class imbalance issues due to the boom in game velocity. A simple and smooth GUI is supplied for smooth gameplay. The gameplay layout is so simple that user won’t discover it tough to use and understand. Different images are used within the development of this easy recreation project, the gaming environment is similar to the authentic T-Rex Dino Run sport. In order to run the project, you need to have set up python and pygame in your PC. This might be a new word for many however each and every one of us has learned to stroll the usage of the idea of Reinforcement Learning (RL) and this is how our brain still works. A reward gadget is a foundation for any RL algorithm.